Problem of Research in Islamic Economics - Khairunnisa Khairunnisa; Revita Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Indonesia is currently the country with the largest Muslim population in the world. The total Muslim population of 80% makes an Islamic-based economy possible to expand widely related to fashion, culinary, tourism, cosmetics, and various topics. Currently, the Indonesian government, practitioners, and academics are working hard to improve the performance of the Islamic finance industry. Understanding that Islamic Economics is only related to Islamic finance is too shallow perception. Many other sectors can be developed, including the hotel business, tourism, culinary, fashion, hotel, other topics. However, research related to the sectors mentioned is very minimal. The phenomenon is happening because most Islamic economic research worldwide discusses topics related to the financial sector. The researchers have been interested in discussing the development of research on Islamic Economics at the University of Muhammadiyah North Sumatra (UMSU) for the last four years. The research is descriptive because the existing data is not processed to accept or reject the hypothesis. The sample selection criteria in this study are all UMSU student thesis related to Islamic economics for the last four years from 2017 – 2020. The results of the study found that out of 499 theses, the majority of students’ research was around the theme of Islamic banking, which was 78%, other themes (including MSMEs, e-commerce, Sharia marts) were 6%, the ZISWAF theme and Halal Industry got the same percentage. Namely, 5 – 6%, the Islamic Capital Market theme at 3.4%, the Fashion and Cosmetics theme at 2%, and the Insurance theme at only 0.8%. considering the current research conditions, it is time for the study program to develop Islamic economic research outside Islamic banking.